VIDEO ANIMASI PROSEDUR PENDAFTARAN MAHASISWA BARU DI UNIVERSITAS MAHAKARYA ASIA BATURAJA MENGGUNAKAN ADOBE FLASH CS6 - Ariyadi, Putra; Suryanto, Suryanto; Rusidi, Rusidi (JIK : Jurnal Informatika dan Komputer, 2023)
Animated Video is a series of pictures taken of moving objects. The image is then projected onto a screen, and loaded at a certain speed so as to produce a live image. The lack of outreach media for prospective new students regarding the steps for registering at Mahakarya Asia Baturaja University causes them to find it difficult to register. Registrants feel confused in finding out step-by-step information that must be done to be officially registered at Mahakarya Asia Baturaja University. Animation can be used to provide clear information in an interesting and easy-to-understand way for prospective new students who wish to register themselves at Mahakarya Asia Baturaja University. Therefore the author tries to make an Animation Video for New Student Registration Procedures at Mahakarya Asia Baturaja University Using Adobe Flash CS6.The data collection methods used in making the Animation Video for New Student Registration Procedures at Mahakarya Asia Baturaja University Using Adobe Flash CS6 are the Interview method, the Reference method, and the Observation method.The result of this final project research is the creation of an animated video entitled Video Animation of New Student Registration Procedures at Mahakarya Asia Baturaja University Using Adobe Flash CS6.